Perhatian Tubuh dalam Bingkai Festival - Ganter Hanggayuh P.P. (Universitas Gadjah Mada, 2019)
Studies on the festival are much found, both traditional and modern festivals. However, there are still many focus points that discuss management and governance, especially in an organization. We know that the festival is a moment which is an event to break the time and space temporarily in real time. At least there are certain techniques that unconsciously ‘capture’ what we are seeing and feeling as personal experiences. Then the part that constructs our understanding of what message the organizer communicates. Need to be examined further when reviewing a festival would be very important to categorize the form of the festival. This paper tries to find opportunities to examine the festival through the response of the performer and audience with a focus on body attention. Moreover, the audience is a member of a community and actively participates in festivals (outside the committee) which actually always emphasizes culture. Some of the possibilities that have been described in this paper can be stimulus to start viewing a festival from the attention of the body of the audience, participants, performer as well as what is involved in the scope of the festival. In addition, this paper highlights the festival through its community, social movements, expressive culture, individual bodies, social bodies, and interactions between bodies as a methodological offer in groping and sorting out what are likely to be studied.